Philippine literature: through the years - Kahayon, Alicia H.; Zulueta, Celia A. (Mandaluyong City, 2000)
An introduction to the study of Philippine literature -- The pre-spanish period(1565) -- The spanish period -- The period of enlightenment -- The american regime(1898-1941) -- The japanese period 1941-1945 -- The rebirth of freedom 1946-1970 -- Period of activism (1970-1972) -- Period of the new society -- Period of the third republic 1981-1985 -- Periods 1986 -- Representative compositions through the years (1989-85) Philippine literature through the years is a beginner's incursion into Philippine Literature.Its aim is to present the historical transition of literature through randomly-selected pieces which we deemed interesting pieces for literary absorption whether for appreciation or for interpretative analysis.
Keywords: Phlippine literature